Religion and Sanitation Practices - Adukia, Anjali; Alsan, Marcella; Babiarz, Kim; Goldhaber-Fiebert, Jeremy D.; Prince, Lea (World Bank, Washington, DC, 2020)
Infant mortality among Hindus is higher than among Muslims in India, and religious differences in sanitation practices have been cited as a contributing factor. To explore whether religion itself is associated with differences in sanitation practices, this study compares sanitation practices of Hindus and Muslims living in the same locations using three nationally-representative data sets from India. Across all three data sets, the unconditional religion-specific gap in latrine ownership and latrine use declines by approximately two-thirds when conditioning on location characteristics or including location fixed effects. Further, the estimates do not show evidence of religion-specific differences in other sanitation practices, such as handwashing or observed fecal material near homes. Household sanitation practices vary substantially across areas of India, but religion itself has less direct influence when considering differences between Hindus and Muslims within the same location.